Self-Handicapping as a Coping Strategy: Approaches to Conceptualization - Nosenko, Dina; Arshava, Iryna; Nosenko, Eleonora (Advances in Social Sciences Research Journal, 2014)
Self –handicapping has been conceptualized by the majority of the authors as a motivational strategy reflecting the efforts of the individual who anticipates failure in dealing with some significant goal-oriented activity to defend one’s sensitive ego.The objective of this research was to substantiate a conceptualization of self-handicapping as a maladaptive proactive coping strategy that opposes a set of other proactive coping strategies , singled out by now, all of which result in positive outcomes, such as preventive, strategic, anticipatory and other forms of constructive proactive coping. Using the statistical methods of correlation and factor analysis, it was found on a sample of 135 university undergraduates, that the personality precursors of self-handicapping and adaptive forms of proactive coping appeared to be orthogonal. While self –handicapping is determined by the high level of neuroticism, low level of ego-involvement (strive to self-evolution), low ego-identity (belief in self-efficacy), the proactiive adaptive coping strategies have shown strong positive correlations with ego-identity (self- esteem, belief in self-efficacy) and ego-involvement, and negative correlation with neuroticism. This proves that self-handicapping complements the system of proactive forms of coping strategies .